IMPLEMENTATION OF SOCIAL REHABILITATION PROGRAM POLICY FOR NARCOTICS INMATE (CASE STUDY PURWOKERTO CLASS IIB NARCOTICS PRISON) - Warih, Wido Cepaka; Setiawan, Eka Fitri (Journal of Social Politics and Governance (JSPG), 2024)
The aim of this research is to examine the implementation of policies regarding social rehabilitation activities for narcotics inmates in prison by taking the research focus at the Purwokerto Class IIB Narcotics Prison. Social rehabilitation is a process of integrated recovery activities, both physical, mental, and social, so that former narcotics addicts can return to carrying out social functions in community life. This study uses a qualitative research approach. The aim of descriptive qualitative research is to create systematic, factual, and accurate information about the facts and characteristics of a particular population or region. The focus of this research is to look at the implementation of social rehabilitation carried out in prisons. Data sources used include interviews, previous research literature, and literature studies. The research results show that the implementation of the social rehabilitation program for narcotics prisoners is effective in terms of the policy/program content dimension and the implementation context dimension. The implications of this research are to provide an overview of whether the social rehabilitation program for narcotics prisoners implemented in correctional institutions is effective or not from a policy perspective.